Canadian Thoracic Society Asthma Management Continuum – 2010 Consensus Summary for Children Six Years of Age and Over, and Adults. Issue 1 (2010) - Lougheed, M Diane; Lemière, Catherine; Dell, Sharon D; Ducharme, Francine M; FitzGerald, J Mark; Leigh, Richard; Licskai, Chris; Rowe, Brian H; Bowie, Dennis; Becker, Allan; Boulet, Louis-Philippe
Abstract : BACKGROUND/OBJECTIVE: To integrate new evidence into the Canadian Asthma Management Continuum diagram, encompassing both pediatric and adult asthma. METHODS: The Canadian Thoracic Society Asthma Committee members, comprised of experts in pediatric and adult respirology, allergy and immunology, emergency medicine, general pediatrics, family medicine, pharmacoepidemiology and evidence-based medicine, updated the continuum diagram, based primarily on the 2008 Global Initiative for Asthma guidelines, and performed a focused review of literature pertaining to key aspects of asthma diagnosis and management in children six years of age and over, and adults. RESULTS: In patients six years of age and over, management of asthma begins with establishing an accurate diagnosis, typically by supplementing medical history with objective measures of lung function. All patients and caregivers should receive self-management education, including a written action plan. Inhaled corticosteroids (ICS) remain the first-line controller therapy for all ages. When asthma is not controlled with a low dose of ICS, the literature supports the addition of long-acting beta2 -agonists in adults, while the preferred approach in children is to increase the dose of ICS. Leukotriene receptor antagonists are acceptable as second-line monotherapy and as an alternative add-on therapy in both age groups. Anti-immunoglobulin E therapy may be of benefit in adults, and in children 12 years of age and over with difficult to control allergic asthma, despite high-dose ICS and at least one other controller. CONCLUSIONS: The foundation of asthma management is establishing an accurate diagnosis based on objective measures (eg, spirometry) in individuals six years of age and over. Emphasis is placed on the similarities and differences between pediatric and adult asthma management approaches to achieve asthma control.